Gramsci’s Concept of Hegemony and Social Formation in Early Colonial Queensland - Howard le Couteur (Limina: A Journal of Historical and Cultural Studies, 2000)
The concepts of hegemony, historical bloc, and civil and political society were developed by Antonio Gramsci to explore the ways in which political power is grasped and maintained. His ideas also cover the ways in which force/coercion and fraud/corruption enter the political process. This study first examines Gramsci’s concepts and then uses them as an interpretive framework to explore the exercise of political power in early colonial Queensland. It identifies several groups which were involved in the political process and who comprised those groups; it examines some of the issues that were important to them ideologically; and then demonstrates how those issues became areas of contention in the search for political power. Gramsci’s ideas are seen to be useful in the characterisation of the colonial political process.